Determinants of Nurses' Knowledge Toward the Elderly Care, Southwest, Ethiopia - Mehd Abdu MSc; Tariku Daniel MSc; Mohammed Yesuf MSc (SAGE Publishing, 2024)
Introduction Elderly individuals are the segment of the population that needs special care. The quality of care provided for elderly individuals is highly determined by the knowledge of nurses in elderly care. Hence, there are limited studies conducted to determine the level of knowledge of nurses regarding elderly care. Therefore, this study aimed to assess determinant factors of nurses' knowledge of elderly care. Methods A facility-based cross-sectional study design was employed from April 1 to 10, 2021, among 345 nurses. Respondents were selected by a simple random sampling technique. The data were collected through a self-administered structured questionnaire. The collected data were entered and analyzed by using Statistical Package for Social Science software version 25.0. A multivariable binary logistic regression was used to identify factors significantly associated with the knowledge of nurses about elderly care. Result The response rate of this study was 98.3%. More than half of the respondents were female (51.6%) and 38.3% were single in marital status. Being knowledgeable among nurses about elderly care was 51.9%. Ever living with the elderly (adjusted odd ratio [AOR]: 3.62; 95% CI: 1.661, 7.89) and taking geriatric care training (AOR: 5.209, 95% CI: 2.771, 9.79) were positively associated with the knowledge of nurses toward elderly care while work experience <5 years (AOR: 0.305; 95% CI: 0.134, 0,696), and work experience 5-10 years (AOR: 0.359; 95% CI: 0.15, 0.864) were negatively associated with the knowledge of nurses toward elderly care. Conclusion The knowledge of nurses about elderly care was moderate. Ever lived with the elderly, work experience, and taking geriatric care training contributed to nurses' knowledge about elderly care. Therefore, hospital administrators and the Ministry of Health should facilitate training, design, and implement standard guidelines on nursing practice for elderly care.